(untitled) (Portuguese Journal of Family Medicine and General Practice, 2014)
The increasing prevalence of mental disorders, their costs, and the effects of the current economic crisis reinforce the need for psychological intervention in medical care. The World Health Organization (WHO) has stated that half of all the suffering associated with health and disease in Western countries is due to mental disorders, particularly depression and anxiety. Research has demonstrated the effectiveness of psychological interventions. The benefits of psychological intervention can occur in conditions not necessarily related to mental disorders such as cardiovascular diseases, cancer, rheumatoid arthritis, diabetes, chronic pain, and others. These benefits cause a reduction in the use of medical services and the use of medication, and promote greater adherence to therapy, as well as behavioral change. Cognitive therapy has low costs and a high success rate. Interest in mental health and the conditions caused by mental distress motivated the author to explore different types of psychotherapy that could be effective in primary care. The family physician can make use of some of the techniques of cognitive therapy. However time devoted to psychotherapy in parallel to the usual medical consultation may complement it. Application of CBT techniques in psychotherapy enhances medical practice and contributes to the whole-person approach.